Evaluation of finite element analysis steel fabric reinforced concrete wall panel / Mohd Suhelmiey Sobri - Sobri, Mohd Suhelmiey (Faculty of Civil Engineering, 2008)
Steel fabric reinforced concrete wall panel is the new method currently used to replace the conventional wall. The formwork used for the construction of the wall is replace by using tunnel form system. It is fast and cost effective compared to the conventional and some other methods. Steel fabric which also known as wire mesh are used as the reinforcement for the wall panel. It is practically provide a faster installation compared to normal bars. Since this method is still new in Malaysia, a specific guide of this method is not established yet to use as a guideline in designing the building structures. Then, the study of this structural element analysis needs to be carried out. This research will compared the structural performance of steel fabric reinforced concrete wall panel and to analyzed t e structural capacity and mode of failure of steel fabric reinforced concrete wall panel by previous researcher. This research used Finite Element Method computer program LUSAS 13.6 as a tool to analyze the wall panel The 3-Dimensional model of steel fabric reinforced concrete wall panel with double layer of wire fabric type B7 with half of actual size 75 x 1000 x 1500 mm and 150 x 3000 x 3000mm (Width:Length:Height) was simulated. This model assigned assigning concrete Grade C30 (BS 8110:1997) and strength characteristic, fy= 485 N/mm2 for the steel fabric reinforcement. The wall panel will analyzed by different of dimension of wall, wall panel supported, loading distribution and with different eccentricity. Through this research, the structural behavior of steel fabric reinforced concrete wall panel using finite element analysis and the result obtained from the analysis can explain the structural behavior of the wall panel. Therefore, it is successful to investigate the effect of the eccentric load and the different of supported to the wall panel and the objective of the research has been complying.